Туристичний потенціал м. Мукачеве на основі порівняння закладів розміщення за статистичними даними та даними системи Booking.com - Товт Атілла; Фодор Дюло; Бергхауер Олександр; Tóth Attila; Fodor Gyula; Berghauer Sándor (Вежа-Друк, 2017)
Резюме. Розглядаються дані, пов’язані із закладами тимчасового розміщення у м. Мукачеве. Порівнюється інформація різних статистичних збірників з електронними ресурсами. Отримані результати аналізуються з географічної точки зору.

Abstract. The present paper deals with the data concerning the commercial quarters in the town of Mukacheve (Transcarpathia, Ukraine). The information of various statistic publications is compared to that of the Internet-resources. The results obtained are analyzed from the geographic point of view.
Touristic Potential of the Town of Mukacheve Based on the Comparison of Commercial Quarters by Statistic Data and the Data of the Booking.com System
Keywords: Booking.com; тимчасові заклади розміщення; статистика; Закарпаття